Aeromonas hydrophilia-infected nonunion of a closed tibial fracture in a healthy adolescent: A case report. (25th May 2021) - Hsu, Wei-Kuo; Chou, Yi-Chuan; Chuang, Chang-Han; Li, Chia-Lung; Wu, Po-Ting
Aeromonas hydrophilia can cause soft tissue infection in both immunocompromised and healthy persons. A healthy 15-year-old adolescent fell into a ditch after a scooter accident and sustained a right distal tibial shaft closed fracture, a right femoral shaft closed fracture, and a dirty laceration over the medial aspect of the distal thigh above the right knee. After empiric antibiotics and radical debridement of the contaminated wound, a femoral interlocking nail and tibial external fixator were applied. However, acute osteomyelitis later presented in his femur and tibia, and Aeromonas hydrophilia grew in cultures from the knee wound and the fracture sites. During the follow-up, his tibia became an infected nonunion, and was successfully treated with the induced membrane technique. In an otherwise healthy patient with a closed fracture, Aeromonas hydrophilia can cause acute osteomyelitis and necrotizing fasciitis by spreading from a nearby contaminated wound. Exposure to water is a risk factor for Aeromonas hydrophilia infection.